Companion Involvement as a Practice for Addressing Patient Resistance: The Case of Traditional Chinese Medicine - Wei, Wan (Social Interaction. Video-Based Studies of Human Sociality, 2024)
Previous research highlights how the presence of companions can influence the trajectory and outcome of medical encounters. This study, set within the context of Traditional Chinese Medicine (TCM), examines cases where medical professionals enlist patient companions to join the consultation when patients resist the doctors’ medical opinions. Results from this study indicate that when companions participate in this manner, they face the dilemma of either endorsing the doctors and aiding in the implementation of their medical agenda or siding with the patients and being a supportive companion. This may explain why this practice is not always effective in countering patient resistance and securing patient adherence, especially when the patient’s resistance is overt and strong.